Nurses' knowledge and therapeutic communication in hospital - Magdalena Jublina Moykari; Mareta Rodame Sinaga; Vanessa Sakke'; Ineke Patrisia; Chriska Roully Adeline Sinaga (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to identify the correlation of nurses' knowledge with the application of nurses' therapeutic communication in hospitals. Methods: a descriptive quantitative, correlational design with a total sampling method was used in the study. Respondents were 68 nurses working in an inpatient room in one of the general hospitals in western Indonesia. Modified questionnaires were used in data collection. Analysis of the Pearson chi-square test was used in data analysis. Results: nurses with sufficient and poor knowledge have a good application of therapeutic communication. There was no correlation between knowledge and the application of nurses' therapeutic communication. Conclusions: therapeutic communication is influenced by many factors, but nurses' knowledge should be maintained and improved to provide holistic care and increase patient satisfaction.